FAKTOR-FAKTOR MIGRASI SUKU BATAK DI KOTA MANADO - Kristina Siboro; Kalvin Salindeho Andaria; Ellen Eva Poli (Jurusan Pendidikan Geografi Universitas Negeri Manado, 2022)
The focus of this research is the migration factor of the Batak tribe in Manado City in terms of push factors, inhibiting factors, and pull factors. The research method used is descriptive qualitative. Research informants are Batak people who live in Manado City with purposive sampling with adult criteria, have families with different occupations, and have lived for a long time. Data collection techniques through observation, interviews, and documentation. Data analysis used a qualitative approach with the stages of data collection, data reduction, data presentation, and concluding. The results of the study explain that the driving factors for the migration of the Batak tribe in the city of Manado were identified due to high competition in work while there are fewer job opportunities in the area of ​​origin, job demands, carrying out the educational process outside the area, looking for work, joining family or friends, and the existence of a culture that states Parent's property does not belong to the child so it demands independence. The inhibiting factors are long-distance, high cost of living, and lack of relationships. While the pull factor is that they are more able to compete in business and work. Another pull factor is the ease of spiritual service and good educational facilities. Another factor is that the people of Manado city are very tolerant, open, friendly, and heterogeneous so that they are comfortable